2013
DOI: 10.6061/clinics/2013(05)04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the tocotrienol-rich fraction on the lifespan and oxidative biomarkers in Caenorhabditis elegans under oxidative stress

Abstract: OBJECTIVE:This study was performed to determine the effect of the tocotrienol-rich fraction on the lifespan and oxidative status of C. elegans under oxidative stress.METHOD:Lifespan was determined by counting the number of surviving nematodes daily under a dissecting microscope after treatment with hydrogen peroxide and the tocotrienol-rich fraction. The evaluated oxidative markers included lipofuscin, which was measured using a fluorescent microscope, and protein carbonyl and 8-hydroxy-2′-deoxyguanosine, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The results about both major components in AE point to dT3 as the main compound responsible for the protective effect; however, this protection can be enhanced by an accumulative effect when bixin is present, which suggests an independent mechanism for each compound. The protective effects of α-tocopherol: tocotrienol mixtures have previously been studied by Adachi and Ishii [26] and by Aan et al [27]. These authors reported an increase in median life as well as resistance to UV and oxidative (H 2 O 2 ) stress, which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The results about both major components in AE point to dT3 as the main compound responsible for the protective effect; however, this protection can be enhanced by an accumulative effect when bixin is present, which suggests an independent mechanism for each compound. The protective effects of α-tocopherol: tocotrienol mixtures have previously been studied by Adachi and Ishii [26] and by Aan et al [27]. These authors reported an increase in median life as well as resistance to UV and oxidative (H 2 O 2 ) stress, which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that UV radiation is the main cause of photoaging and induces cell and tissue damage as the production of ROS, which leads to DNA damage [36]. In this sense, CSE could be reducing the oxidative stress accumulation and, therefore, the DNA damage, as previously demonstrated with other antioxidant compounds, such as tocotrienol [37]. Although previous reports have been made about the functional properties of coffee in C. elegans [38,39], we report for the first time the potential of a natural extract from coffee silverskin by-product for UV radiation protection, which could be very interesting for dermo- and nutria-cosmetic companies developing new products targeting photoaging.…”
Section: Discussionmentioning
confidence: 86%
“…But, if DNA damage is localized to only intestinal cells (less than 1% of the DNA content of a fertile hermaphrodite), we would not expect to see a dramatic change in 8-OHdG as measured for the entire DNA content of a C. elegans. In published experiments, treatment of C. elegans with hydrogen peroxide, a known agent promoting formation of 8-OHdG (37), resulted only in a modest increase in , from 20 to 25 pg per microgram of chromosomal DNA, despite high dosage of hydrogen peroxide and lengthy treatment (38). Thus, our results should not be interpreted as an absence of a change in 8-OHdG as this assay might not be sensitive enough to reveal the change in chromosomal DNA of intestinal cells.…”
Section: Feeding With Rhizobium Disrupts Karyokinesis During Larval Smentioning
confidence: 99%